Ikon, Indeks, dan Simbol dalam Cerpen Tiga Cerita tentang Lidah Karya Guntur Alam - Dewi Ratnaningsih; Rahmat Prayogi (Universitas Muhammadiyah Kotabumi, 2020)
This article discusses icons, indexes, and symbols in a short story. The semiotic approach is used as a literary approach to discuss this. The short story to be analyzed is the short story Three Stories About the tongue by Guntur Alam. The titles are (1) the death of the bitter tongue, (2) the tongue which tells of jurai; (3) Storyteller Tongue Wars. Each story title will be analyzed using icon, index, and symbol theory. Following is the explanation of the analysis results of the three story titles. Study of icons, indexes, and symbols in the death of the bitter tongue. The icon in the story of the death of the bitter tongue can be seen from the word